THE MEMORY OF THE BODY AS TRANSPERSONAL ARCHETYPE - Lucaciu, Adriana (Design/Arts/Culture, 2023)
The paper proposes a perspective based on a research through art at the crossroads between personal memory, corporeality, transpersonal archetypes and drawing. If art can be admitted as a way of ‘writing’ through images, self-reflexive art can be considered a self-description, as well as an ‘autograph’, which is not reduced to affectivity. From here it is only a step to notice that the ‘disguised’ revelation of the self as our memory archived it, by artistic works, turns out to be a symbolic narrative, expressed through metaphors with autobiographical overtones. The artistic act placed outside of creation in relation to the evaluative factors, is exempt from gratuity because it responds to at least one existential need – that of self-expression, which becomes paramount in historical, social and private history contexts. It plays a main role in documenting actual life and preserving it for the future, like reveries of dissolution and permanence.